Game programming using Qt : a complete guide to designing and building fun games with Qt and Qt Quick 2 using their associated toolsets : beginner's guide /: a complete guide to designing and building fun games with Qt and Qt Quick 2 using their associated toolsets : beginner's guide. (2016) - Wysota, Witold; Haas, Lorenz
No abstract available